Molecular characterization of Ralstonia solanacearum strains from Ethiopia and tracing potential source of bacterial wilt disease outbreak in seed potatoes - Abdurahman, A.; Griffin, D.; Elphinstone, J.; Struik, P.C.; Schulz, S.; Schulte-Geldermann, Elmar; Sharma, K. (Wiley, 2017)
Bacterial wilt, caused by Ralstonia solanacearum, is emerging as a major threat to potato production in Ethiopia, reaching epidemic proportions in the Chencha district recently, with a prevalence of 97% of potato fields in 2015. The recent disease outbreak in the district coincided with a significant introduction of seed potatoes. This research was therefore initiated to genetically characterize the pathogen so as to trace its source, identify its relationship with outbreaks in the rest of the country, and make intervention recommendations. Ralstonia solanacearum isolates were sampled both from seed and ware potato fields in Chencha and from seed potato fields in production regions suspected of being potential sources of the pathogen. Multiplex PCR and phylogenetic analysis of partial endoglucanase gene sequences identified all of the isolates as phylotype IIB sequevar 1. VNTR sequence analysis distinguished 11 different haplotypes, nine of which were unique to the Chencha district. However, one of the haplotypes was common to all seed potato producer regions of Ethiopia except for the Shashemene area. The unique and diverse VNTR haplotypes of the pathogen in Chencha indicates that it is well established in the district. When a geographical map of the VNTR haplotypes was superimposed with the main cross-regional seed potato distribution pattern of the country, it became evident that the pathogen was being disseminated via latently infected seed from the Holeta-Jeldu area in the Central Highlands of Ethiopia. Identification of largely uninfected highland districts and multiplication of high grade seed potato exclusively in those districts should be given priority.